Prognostic impact of pre-existing interstitial lung disease in non-HIV patients with Pneumocystis pneumonia. Issue 2 (4th May 2020) - Hamada, Shohei; Ichiyasu, Hidenori; Inaba, Megumi; Takahashi, Hiroshi; Sadamatsu, Tomoki; Akaike, Kimitaka; Masunaga, Aiko; Tashiro, Yasumasa; Hirata, Naomi; Yoshinaga, Takeshi; Sakagami, Takuro
Background: The increasing incidence of life-threatening Pneumocystis pneumonia (PCP) in non-HIV immunocompromised patients is a global concern. Yet, no reports have examined the prognostic significance of pre-existing interstitial lung disease (ILD) in non-HIV PCP. Methods: We retrospectively reviewed the medical records of non-HIV PCP patients with (ILD group) or without (non-ILD group) pre-existing ILD. The clinical features and outcomes of the ILD group were compared with those of the non-ILD group. Cox regression models were constructed to identify prognostic factors. Results: 74 patients were enrolled in this study. The 90-day mortality was significantly higher in the ILD group than in the non-ILD group (62.5% versus 19.0%, p<0.001). In the ILD group, patients with a higher percentage of bronchoalveolar lavage fluid neutrophils had worse outcomes compared to those having a lower percentage (p=0.026). Multivariate analyses revealed that pre-existing ILD (p=0.002) and low levels of serum albumin (p=0.009) were independent risk factors for 90-day mortality. Serum levels of β-d -glucan were significantly reduced after treatment of PCP in both groups, whereas levels of Krebs von den Lungen-6 (KL-6) significantly increased in the ILD group. In the ILD group, the 90-day mortality of patients with increasing KL-6 levels after treatment was significantly higher than those with decreasing levels (78.9% versus 0%, p=0.019). Conclusion: In non-HIV PCP patients, pre-existing ILD is associated with a poorer prognosis. Prophylaxis for PCP is needed in patients with pre-existing ILD under immunosuppression. Pre-existing interstitial lung disease (ILD) is an independent prognostic risk factor for non- HIV Pneumocystis pneumonia (PCP). Prophylaxis for PCP is needed in patients with pre-existing ILD under immunosuppression. http://bit.ly/37BGZuK